Primary Cutaneous Mucinous Carcinoma of the Left Zygomatic Region: A Case Report - Huang Q; Niu M; Xiong X; Tang N; Wen W (Clinical, Cosmetic and Investigational Dermatology)
Qingan Huang,1,* Mu Niu,2,* Xifeng Xiong,3 Nan Tang,4 Weilun Wen4 1Department of General Ward, The Fifth People’s Hospital of Hainan Province, Haikou, Hainan, People’s Republic of China; 2Department of Cosmetic Dermatology, The Fifth People’s Hospital of Hainan Province, Haikou, Hainan, People’s Republic of China; 3Guangzhou Institute of Traumatic Surgery, Guangzhou Red Cross Hospital of Jinan University, Guangzhou, Guangdong, People’s Republic of China; 4Departments of Traditional Chinese Medicine, Guangzhou Red Cross Hospital of Jinan University, Guangzhou, Guangdong, People’s Republic of China*These authors contributed equally to this workCorrespondence: Weilun Wen; Nan Tang, Departments of Traditional Chinese Medicine, Guangzhou Red Cross Hospital of Jinan University, Guangzhou, Guangdong, People’s Republic of China, Email 735616613@qq.com; tangnan813@163.comAbstract: We describe a case involving a 50-year-old male with who presented with a facial lesion on the left cheek of zygomatic region for 7 years. The diagnosis of primary cutaneous mucinous carcinoma (PCMC) was established through immunohistochemistry and histopathology. And the patient underwent wide excision of the tumor, has no evidence of recurrence after 15 months of follow-up.Keywords: primary cutaneous mucinous carcinoma, immunohistochemistry, histopathology